Consumption Externalities and the Role of Government: The Case of Alcohol - Felicity Barker (New Zealand Government, The Treasury, 2002)
This paper considers the role of government in the case of externalities and, in particular, in the case of alcohol externalities. The purpose of the paper is to assess whether the current level of the alcohol excise can be justified on externality grounds. The paper assesses various mechanisms to address externalities. These mechanisms are institutional solutions, trade in rights to generate externalities, regulatory measures and Pigouvian taxes. The paper assesses these tools in the case of alcohol and concludes that institutional, trade and regulatory solutions are limited in their ability to address the externalities of alcohol. A specific tax can be justified in the case of alcohol. The externalities are large and there is sufficient information on which to base a tax. Given the information constraints the specific tax must be applied uniformly across a rage of units of consumption, rather than to particular individuals. Where an optimal uniform tax is imposed it is reasonable to assume that the amount of revenue collected by the government would be at least as large as the total externality. In 1999/00 the amount of revenue collected from the tax on alcohol was 580 million. This is near the mid-point of the estimated bound of the external tangible costs of alcohol. Thus the current rate of excise tax can be justified on externality grounds.
Keywords: D11; H11; H23; 330; Externalities; Alcohol; Coase theorem; Pigouvian tax